Overview of Domestic Rape Jurisdiction (Decision Number 899/Pid.Sus/2014/PN.Dps) - Umami, Naily Kharisatul (Pusat Pengkajian Pancasila dan Konstitusi (PUSKAPSI) FH UNEJ, 2022)
Sexual violence against wives that occurs in the household is better known by the general public as marital rape which is defined as rape that occurs in a marriage bond. However, a broader understanding understood by various groups regarding marital rape is a wife who receives acts of sexual violence by her husband or coercion by all against her wife to carry out sexual activities without considering the condition of the wife. Or forcing to have sexual relations in ways that are not fair or do not like the wife. In Indonesia, there have been several court decisions regarding the issue of sexual violence in the household, one of which is Decision Number 899/Pid.Sus/2014/PN.Dps which was carried out by Tohari. The panel of judges in deciding this case using Article 46 of Law no. 23 of 2004 concerning the Elimination of Domestic Violence The judge's considerations are in accordance with the legal facts that have been proven by the public prosecutor that the defendant intentionally committed an act of domestic violence that caused physical injury to the victim's body and genitals. And the elements have been fulfilled, namely the element of every person and the element of committing acts of sexual violence. Of the aggravating and mitigating factors, one of the aggravating factors was that the defendant had hurt and injured the victim's witness who was the defendant's wife and the defendant did not feel guilty about what he had done. While mitigating factors are the defendant has never been convicted and the defendant is elderly. Therefore, based on the facts and legal considerations, the panel of judges sentenced the defendant to 5 (five) months in prison from the original demand of 10 (ten) months from the public prosecutor.